Improvement of organizational and documentary security of vacation - Dubinina, Maryna; Cheban, Yuliia; Horbach, Svitlana; Dubinin, Viktor (Technology audit and production reserves, 2017)
The object of research is a system of organizational and documentary support for the design and provision of vacations in agricultural enterprises. One of the most problematic places is that ... information about the specifics of granting and documenting vacation, as well as their main types at enterprises and the amount of supply is not subject to official sources of the State Statistics Committee. Such information is not displayed in the reporting forms of enterprises, which requires the use of additional methods and sources of information collection. An experience of foreign countries to use vacation as one of the methods of motivating employees is used in the research. The introduction of an internal document into the activities of enterprises, which can have a form that is independent of other documents, and be part of the internal social report of the enterprise. The following generalized elements are defined as «vacation»: dismissal of the employee from performance of labor duties, preservation of the employee in the period of vacation of employment (position), payment. It is established that the term «vacation» is identified with the concept of «time». The main features of the majority of vacations are formulated. The main directions of improving the organizational and documentary provision of vacation and its use in the context of social activities of enterprises are outlined, namely: – use of vacation as one of the types of employee motivation; – use of the classification of vacations to improve its planning, analysis and control; – recording information on vacations in collective agreements of enterprises; – use of an internal document to display information on the volume of species, sources of coverage for vacation expenses.